Strategy to Improve Hospital Human Resource Performance Through Analysis of Patient Service Data in Private Hospitals in Gresik - Iqbal Razif; Mundakir Mundakir; Annisa Nurida (International Journal of Public Health, 2026)
Background: Hospitals are required to provide fast, accurate, and high-quality healthcare services to improve patient satisfaction and maintain organizational competitiveness. Human resource (HR) performance plays a crucial role because healthcare workers directly interact with patients during service delivery. Objective: This study aims to analyze the influence of service intensity and hospital revenue on patient volume as an indicator of HR performance in a private hospital in Gresik. Methods: A quantitative descriptive approach was used with secondary data from the hospital information system, including patient service records, physician services, transaction values, hospital revenue, and service units. Data were analyzed using descriptive statistics, correlation analysis, multiple linear regression, R², t-test, and F-test. Results: Service intensity showed a positive and significant effect on patient volume, with a correlation coefficient of 0.530 (p = 0.001) and regression coefficient of 0.460 (p = 0.041), indicating that higher service intensity increases patient volume. Hospital revenue showed a positive correlation with patient volume (r = 0.412; p = 0.011), but regression results indicated no significant effect (β = 0.394; p = 0.633). Simultaneously, both variables significantly influenced patient volume (F = 5.624; p = 0.009), with R² = 0.287. Conclusion: Service intensity is the dominant factor affecting patient volume and serves as an important indicator for HR performance improvement. Strengthening service quality, workforce allocation, and healthcare analytics is recommended to enhance hospital performance and patient outcomes.